Features of pseudomonads growing at low temperatures: another facet of their versatility. Issue 5 (3rd March 2014) - Moreno, Renata; Rojo, Fernando
Summary Pseudomonads are a diverse and ecologically successful group of γ‐proteobacteria present in many environments (terrestrial, freshwater and marine), either free living or associated with plants or animals. Their success is at least partly based on their ability to grow over a wide range of temperatures, their capacity to withstand different kinds of stress and their great metabolic versatility. Although the optimal growth temperature of pseudomonads is usually close to 25–30°C, many strains can also grow between 5°C and 10°C, and some of them even close to 0°C. Such low temperatures strongly affect the physicochemical properties of macromolecules, forcing cells to evolve traits that optimize growth and help them withstand cold‐induced stresses such as increased levels of reactive oxygen species, reduced membrane fluidity and enzyme activity, cold‐induced protein denaturation and the greater stability of DNA and RNA secondary structures. This review gathers the information available on the strategies used by pseudomonads to adapt to low temperature growth, and briefly describes some of the biotechnological applications that might benefit from cold‐adapted bacterial strains and enzymes, e.g., biotransformation or bioremediation processes to be performed at low temperatures.